Global street economy and micro entrepreneurship - Grima, Simon; Sirkeci, Osman; Elbeyoğlu, Kamuran (Emerald Publishing Limited, 2020)
Throughout the history of capitalism, street economy has found a space in the failures and externalities of the open market economy, but it has been derided or ignored in the mainstream media and academy. However, street economies are a solution, not a problem: popping up as a spontaneous solution to the failures of capitalism, these economies are an opportunity to learn, explore and grow away from the mainstream. Even though discussion of street economy and vendors is on the rise in recent years, the subject is still dealt with on the basis of sectors, cities and countries, not on a global scale. With the increase in the volume, types and functions of street activities, is has become more appealing for the wider population by including a wide variety of sectors. The studies in this volume of Contemporary Studies in Economic and Financial Analysis investigate the causes and effects of new street-focused formations, such as NASVI in India, and SWG in ILO, established in response to the new legal regulation and organizational needs that have emerged with increasing employment volume in the street economy. For researchers and students of contemporary economics, interested in a global view on a rising industry, this is a key exploration of how micro businesses play on the global level.
Includes index.
Keywords: International economic relations.; Microeconomics.; Entrepreneurship.; Informal sector (Economics); Business & Economics -- International -- Economics.; elektronické knihy; electronic books